Characterization of residual biomass from the harvest of Eucalyptus saligna for thermal conversion processes - Silveira, Joyce Helena da; Dorneles, Ricardo Henrique Thomé; Sebben, Victor Hugo Andreis; Gasparin, Fabiano Perin; Ries, Lúcia Allebrandt da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Considering the increasing need for renewable products, the present work aims to evaluate the physical-chemical properties of the eucalyptus harvest residues and its constituent fractions individually (barks, leaves, and branches), through proximate, ultimate, energetic and thermal analyzes. The biomass studied was Eucalyptus saligna species, cultivated mainly for the production of pulp and paper. The proximate analysis of the residue resulted in the moisture content of 10.1%, ash content of 3.9%, volatile materials about 81.1%, and fixed carbon of 15.0%, showing similar values to the constituent fractions. The ultimate analysis of the residue resulted in 46.5% of carbon content, 5.8% of hydrogen, and 43.2% of oxygen. The high heating value (HHV) for the residue is 17.93 MJ/kg, comparable to other biomasses of importance, including eucalyptus wood, the noblest part of the forest cultivation. The thermogravimetric (TGA) and differential thermal analysis (DTA) were carried out and the resulting thermograms show three main ranges of biomass degradation. The first range, from 30 to 150 °C, corresponds to the drying of the material; in the range from 200 to 325 °C hemicelluloses degrade, with partial degradation of lignin and cellulose, and in the range from 325 to 380 °C, the majority of cellulose degradation takes place. The physical-chemical data demonstrate that the eucalyptus residue is an excellent source of biomass for thermal conversion processes. Obtaining products with higher added value from this residue contributes to the implementation of new technological practices that link economic development to environmental responsibility.